The Relationship Between Medical Staff Education and Hemodialysis Therapy Adherence to Improve Quality of Life in Patients with Chronic Kidney Disease (CKD) at RSUD Menggala - Diajeng Ariwidowati; Endang Budiati; Sugeng Eko Irianto (Knowledge Dynamics, 2026)
Background: Chronic kidney disease (CKD) is a chronic condition that requires routine and continuous hemodialysis therapy. Patient adherence to hemodialysis at RSUD Menggala is crucial to prevent complications and improve quality of life. Various factors are suspected to influence adherence, including environmental factors, educational instruments/media, and individual factors. This study aimed to analyze the relationship between environmental, instrument, and individual factors and adherence to hemodialysis therapy among CKD patients at RSUD Menggala in 2025. Methods: This study used a quantitative analytical cross-sectional design to examine the relationship between healthcare professionals’ educational interventions and adherence to hemodialysis therapy among stage 5 CKD patients at RSUD Menggala in 2025. Data were collected from 84 respondents using structured questionnaires and analyzed using Chi-square and logistic regression tests with SPSS version 26 to identify factors associated with adherence to hemodialysis therapy. Results: The majority of respondents showed moderate to high adherence to hemodialysis therapy. Bivariate analysis revealed significant associations between environmental factors (p=0.004), educational instruments (p=0.003), and individual factors (p<0.001) with adherence. Patients with supportive environments, adequate educational media, and positive individual characteristics were more likely to adhere to therapy. Multivariate analysis showed that individual factors were the most dominant determinant (p=0.001; OR=12.308), indicating that patients with favorable individual factors had more than twelve times higher likelihood of adherence compared to those with unfavorable factors. Conclusion: Individual factors play the most significant role in improving adherence to hemodialysis therapy among CKD patients at RSUD Menggala.